2022
DOI: 10.3389/fmicb.2022.911269
|View full text |Cite
|
Sign up to set email alerts
|

Rahnella sp., a Dominant Symbiont of the Core Gut Bacteriome of Dendroctonus Species, Has Metabolic Capacity to Degrade Xylan by Bifunctional Xylanase-Ferulic Acid Esterase

Abstract: Rahnella sp. ChDrAdgB13 is a dominant member of the gut bacterial core of species of the genus Dendroctonus, which is one of the most destructive pine forest bark beetles. The objectives of this study were identified in Rahnella sp. ChDrAdgB13 genome the glycosyl hydrolase families involved in carbohydrate metabolism and specifically, the genes that participate in xylan hydrolysis, to determine the functionality of a putative endo-1,4-β-D-xylanase, which results to be bifunctional xylanase–ferulic acid esteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…In brief, this study shows that Rahnella isolates associated with the gut of Dendroctonus -bark beetles are an ecotype of R. contaminans . This ecotype is a recurrent, dominant, and persistent symbiont in the gut, which plays a fundamental ecological role in the benefit of these bark beetles, due to its capacity to hydrolyze esters, lipids, and xylans ( Briones-Roblero et al, 2017b ; Pineda-Mendoza et al, 2022 ), as well as recycle uric acid ( Morales-Jiménez et al, 2013 ), and degrade or transform different toxic monoterpenes for insects ( Boone et al, 2013 ; Xu et al, 2015 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, this study shows that Rahnella isolates associated with the gut of Dendroctonus -bark beetles are an ecotype of R. contaminans . This ecotype is a recurrent, dominant, and persistent symbiont in the gut, which plays a fundamental ecological role in the benefit of these bark beetles, due to its capacity to hydrolyze esters, lipids, and xylans ( Briones-Roblero et al, 2017b ; Pineda-Mendoza et al, 2022 ), as well as recycle uric acid ( Morales-Jiménez et al, 2013 ), and degrade or transform different toxic monoterpenes for insects ( Boone et al, 2013 ; Xu et al, 2015 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Hernández-García et al, 2017 ), and it has been persistently reported in all developmental stages of Dendroctonus rhizophagus ( Briones-Roblero et al, 2017a ). Furthermore, it has been shown that Rahnella strains from bark beetles play a fundamental role in the digestive and detoxification processes, since they are capable of degrading different substrates such as esters, lipids, and xylan ( Briones-Roblero et al, 2017b ; Pineda-Mendoza et al, 2022 ), recycling uric acid ( Morales-Jiménez et al, 2013 ), and degrading or transforming different monoterpenes of the host trees of these insects ( Boone et al, 2013 ; Xu et al, 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all of the insect species harboring bacteriocyte symbionts live on nutritionally poor or unbalanced diets, e.g., plant sap, animal blood, and wood (14). The bacteriocyte symbionts can help insects utilize such diets by providing specific nutrients that the insect cannot synthesize, such as essential amino acids (EAAs), B vitamins, and sterols, and by degrading complex plant polysaccharides (16,82,90). The nutritional symbionts in bacteriocytes are indispensable for the normal growth, development, and reproduction of host insects (14,16,32).…”
Section: Bacteriocyte Adaptation For Nutritional Interactions With Sy...mentioning
confidence: 99%
“…Structurally, xylan is not a simple polymer, as it is not only composed of homopolymeric or linear backbone but may also contain branches or side chains, which adds heteropolymeric character to its backbone 29,30 . Monomers of β‐D‐xylopyranosyl are linked in a linear fashion to form homopolymeric long chains, whereas addition of variety of side chains such as o‐acetyl, 4‐O‐methyl‐D‐glucurono‐ pyranosyl, α‐L‐arabinofuranosyl, feruloyl or p‐coumaroyl, and so forth contribute to the formation of heteropolymeric structure 29,31,32 …”
Section: Xylan: the Substrate Of Xylanasementioning
confidence: 99%
“…29,30 Monomers of β-D-xylopyranosyl are linked in a linear fashion to form homopolymeric long chains, whereas addition of variety of side chains such as o-acetyl, 4-O-methyl-D-glucurono-pyranosyl, α-L-arabinofuranosyl, feruloyl or p-coumaroyl, and so forth contribute to the formation of heteropolymeric structure. 29,31,32…”
Section: Xylan: the Substrate Of Xylanasementioning
confidence: 99%